Seed and market systems of the Eastern DRC: A fragile state case study - Templer, Noel; Birachi, Eliud Abucheli; Rubyogo, Jean-Claude (2022)
This report presents one of three case studies undertaken as part of a broader study to explore and develop models for the emergence of enhanced and resilient seed systems in fragile state contexts. Such contexts provide a particular challenge for seed system development. Existing formal seed sector development models are not viable in fragile states due to a severe lack of capacity, insecurity, and ongoing political and economic instability. The formal seed sector is either weak or non-existent in fragile states, and farmers necessarily rely on the informal seed sector. Many also receive seed and related support through emergency interventions. Donor-funded emergency seed provisioning aims to support farmers with access to seed in the short term but often does little to support the emergence of sustainable seed systems in the long term. The question persists of how humanitarian and development actors can work together to enhance the formal, informal, and emergency seed sectors in ways these three components support and strengthen each other in fragile states.